Barriers to and facilitators of pet grooming among clients served by a subsidized grooming service program - McDonald, Shelby E.; Doherty, Colleen; Sweeney, Jessica; Kisiel, Lisa; Matijczak, Angela; Niestat, Laura; Gupta, Maya (Frontiers in Veterinary Science, 2022)
Grooming is an important aspect of basic hygiene care for most companion animals. The consequences of not receiving routine grooming care can pose significant risks to animals’ health and well-being. The current study examined barriers and facilitators of maintaining pets’ grooming needs among clients of a subsidized grooming service program, as well as the impact of a tailored nail-trimming demonstration on clients’ confidence trimming pets’ nails. Ninety-two percent of the sample reported experiencing at least one barrier to maintaining their pet’s grooming and nearly half experienced three or more barriers to providing grooming. Ninety-one percent endorsed that at least one supply/support would be beneficial in maintaining their pet’s grooming needs at home and more than half reported that three or more supplies/services would be beneficial. Differences in the prevalence of specific barriers to grooming were found across income groups, service locations, and service settings. Clients who received nail-trimming demonstrations, on average, reported statistically significant increases in confidence trimming nails following their appointment. We discuss the implications of these findings for improving animal welfare and veterinary professionals’ capacity for preventing grooming-related omissions of care and increasing communities’ capacity to support pet owners’ access to essential pet care supplies and supports.